Analysis of Children’s Traffic Behaviour at Signalized Crosswalks as a Precondition for Safe Children Routes Design: A Case Study from Croatia - Aleksandra Deluka-Tibljaš; Sanja Šurdonja; Irena Ištoka Otković (Journal of Advanced Transportation)
Children pedestrians represent road users with some specifics because of which it is important to study and take into account their traffic behaviour when traffic infrastructure is designed. Design should ensure and enhance their traffic safety because for decades, traffic accidents have been among the first few causes of children and adolescent mortality. Pedestrian speed is one of the important inputs when pedestrian infrastructure, especially crosswalks, is designed. On corridors where children are expected on a daily basis as independent pedestrians, the infrastructure should be adjusted to their characteristics and needs. The results of a study conducted in two Croatian cities of a similar size but of different urban and traffic conditions are presented in this paper. This study aimed at establishing and analysing children’s pedestrian speed while crossing the signalized crosswalk in the buffer area of elementary schools, mostly on primary roads in the school vicinity. Children aged 5–15 were observed, and accordingly V15, V50, and V85 speeds were established on the basis of altogether 600 measurements. Speed was established for children walking individually, in a group and supervised by adults, and of a different age, and based on their gender, the impact of infrastructural elements on their speed in traffic was also analysed. Significant differences were found between children’s speed measured in similar conditions in analysed cities and between some of the analysed groups. This fact proves that when improving conditions for children’s independent movement, it is important to consider their specifics in order to ensure safe design adjusted to children’s needs and limitations. As design speed in this paper, 15 percentile speed (V15) is considered. Suggestions on how to establish children pedestrian speed for design of routes regularly used by school children are proposed as well as some inputs elicited from the study done in Croatia are presented.